The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-88046-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a new highly divergent Mobala related arenavirus isolated from Praomys sp. rodents

Abstract: Arenaviruses represent a family of viruses that are naturally present in rodents belonging to subfamily Murinae, Neotominae or Sigmodontinae. Except for Lassa virus, little information is available on other Old-World arenaviruses. Here, we describe strain AnRB3214, a virus isolated from a presumed Praomys sp. rodent in the Central African Republic in 1981 and assigned to Ippy virus based on antigenic similarity. The strain was simultaneously sequenced on Illumina NovaSeq 6000 and MinION Mk1B devices and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…As reported for other mammarenaviruses, the virus may only be present in the M. natalensis subtaxon A-I 36 , 37 . Records of Lassa virus infection in M. natalensis subtaxon A-II 76 and in other rodent species including M. erythroleucus or Hylomyscus pamfi 77 suggest, however, that susceptibility to Lassa virus infection may not be species or subtaxon specific. Other possible explanatory factors include intra-host competition between different viruses 38 , 78 , or cross-immunity due to the circulation of closely related viruses 40 , 41 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As reported for other mammarenaviruses, the virus may only be present in the M. natalensis subtaxon A-I 36 , 37 . Records of Lassa virus infection in M. natalensis subtaxon A-II 76 and in other rodent species including M. erythroleucus or Hylomyscus pamfi 77 suggest, however, that susceptibility to Lassa virus infection may not be species or subtaxon specific. Other possible explanatory factors include intra-host competition between different viruses 38 , 78 , or cross-immunity due to the circulation of closely related viruses 40 , 41 .…”
Section: Discussionmentioning
confidence: 97%
“…As most other old world arenaviruses that circulate in M. natalensis are found only in East Africa 12 , 36 , 37 , there is little data to assess these two mechanisms based on field data. Only in Mayo-Ranewo (Taraba state, eastern Nigeria), rodent trapping studies have identified a Mobala-like virus in M. natalensis 76 , 79 , which does not seem to effectively restrict the transmission of Lassa virus, as human infections are often reported in that state of Nigeria 80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation